2019
DOI: 10.1029/2019jd031139
|View full text |Cite
|
Sign up to set email alerts
|

MJO Propagation Processes and Mean Biases in the SubX and S2S Reforecasts

Abstract: The Madden‐Julian oscillation (MJO) is the leading source of global subseasonal predictability; however, many dynamical forecasting systems struggle to predict MJO propagation through the Maritime Continent. Better understanding the biases in simulated physical processes associated with MJO propagation is the key to improve MJO prediction. In this study, MJO prediction skill, propagation processes, and mean state biases are evaluated in reforecasts from models participating in the Subseasonal Experiment (SubX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 60 publications
8
60
0
Order By: Relevance
“…Second, the MJO loses its amplitude very quickly in the models considered here, a common problem in forecast models (Kim et al, 2018;Kim et al, 2019;Vitart , 2017). It may be the case that the MJO signal is too weak to be modulated by the QBO.…”
Section: Summary and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, the MJO loses its amplitude very quickly in the models considered here, a common problem in forecast models (Kim et al, 2018;Kim et al, 2019;Vitart , 2017). It may be the case that the MJO signal is too weak to be modulated by the QBO.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…NCAR‐CESM1 reforecasts were carried out using the SubX protocol, but NCAR‐CESM1 does not produce real‐time forecasts. The MJO prediction skills in SubX reforecasts are comparable to those in the S2S project (Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Forecasts less than a month, such as real-time information or near real-time, daily, weekly, and ten-day, are vital for agricultural decision-making. To date, many forecasting models struggle with predictivity below 10 days [36]. Gensini et al [37], found that forecast skills are higher between two-versus three-week lead-time.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, modern developments garner little improvement. The Kim et al (2019) analyses of eight world-class GCMs feature too frequent light precipitation, underestimated heavy precipitation, and early onset of precipitation compared to observations.…”
Section: Introductionmentioning
confidence: 87%